To the fauna of Pterophoridae of Bolivia with a description of three new species (Lepidoptera: Pterophoridae) - P. Ya. Ustjuzhanin; V. N. Kovtunovich; A. N. Streltzov (SHILAP)
The article describes three Pterophoridae species from Bolivia which are new to science: Hellinsia swammerdami Ustjuzhanin & Kovtunovich, sp. n., Hellinsia sergeii Ustjuzhanin & Kovtunovich, sp. n. and Hellinsia aymara Ustjuzhanin & Kovtunovich, sp. n. Nine Pterophoridae species are reported from Bolivia for the first time: Lioptilodes rionegroicus Gielis, 1991, Lioptilodes zapalaicus Gielis, 1991, Stenoptilodes gilvicolor (Zeller, 1877), Exelastis phlyctaenias (Meyrick, 1911), Hellinsia chalupi Gielis, 2013, Hellinsia emmorus (Walsingham, 1915), Hellinsia yalae Gielis, 2013, Adaina bolivari (Căpuşe, 1987) and Adaina hodias (Meyrick, 1908).